Synthesis and characterization of LNMO cathode materials for lithium-ion batteries. (2018) - Ganas, G.; Kastrinaki, G.; Zarvalis, D.; Karagiannakis, G.; Konstandopoulos, A.G.; Versaci, D.; Bodoardo, S.
Abstract: Synthesis of LiNi0.5 Mn1.5 O4 (LNMO), a promising cathode material for next generation lithium-ion batteries, was performed via Liquid Phase Self-propagating High-temperature Synthesis (LPSHS) and Aerosol Spray Pyrolysis (ASP) techniques. In the case of the LPSHS technique, the effect of the "fuel" quantity of the precursor solution on the structure, morphology and electrochemical performance of the materials was studied, while in the case of the ASP technique the effect of eight different calcination profiles on the structure, morphology, crystalline phase and electrochemical performance of the material. Structural characterization was performed through XRD, SEM, TEM, BET and Raman spectroscopy, while the electrochemical activity was evaluated via charge/discharge galvanostatic characterization. The results showed that the optimal LPSHS material was obtained for a molar ratio of metal ions/fuel = 3:1 exhibiting stable specific capacity over the cycles even by increasing the C-rate. Τhe optimal ASP material was identified in the case of calcination at 850°C. Both materials had the disordered Fd -3 m structure of the LNMO spinel